2015 European guideline on the management of Chlamydia trachomatis infections - Lanjouw, E; Ouburg, S; de Vries, H J; Stary, A; Radcliffe, K; Unemo, M (International journal of STD & AIDS, 2016)
Chlamydia trachomatis infections, which most frequently are asymptomatic, are major public health concerns globally. The 2015 European C. trachomatis guideline provides: up-to-date guidance regarding broader indications for testing and treatment of C. trachomatis infections; a clearer recommendation of using exclusively-validated nucleic acid amplification tests for diagnosis; advice on (repeated) C. trachomatis testing; the recommendation of increased testing to reduce the incidence of pelvic inflammatory disease and prevent exposure to infection; and recommendations to identify, verify and report C. trachomatis variants. Improvement of access to testing, test performance, diagnostics, antimicrobial treatment and follow-up of C. trachomatis patients are crucial to control its spread. For detailed background, evidence base and discussions, see the background review for the present 2015 European guideline on the management of Chlamydia trachomatis infections (Lanjouw E, et al. Int J STD AIDS. 2015).